ANALISIS SERIAL ANIMASI “TAKOPI’S ORIGINAL SIN” DALAM PENYAMPAIAN TENTANG MASALAH LINGKUNGAN SOSIAL - Listyawan, Rania Hilmi; Saputra, Anggo Ahmad (Anima Rupa, 2026)
Animation can be briefly described as an attempt to give the illusion of life, such as movement, to inanimate objects by composing the objects into a series of images that are not significantly different from each other, thus producing the illusion of smooth movement. In the past, animation can be only created by using the flip book method, the method is basically playing many images in a short set amount of time so that the images in the book appeared to look like they’re moving. However, as time has progressed, many other animation methods have arrived, for example, CGI and 3D. Regardless of the method that is used to create animation, animation can be a medium to express issues within our society for both young and adult audiences. Takopi’s Original Sin, an animated series from Japan that consist of six episodes, is one of the example on how animation is used for communication media about social issues within our society by visual. The research method I used is literature review, applying reliable statements from various journals and books to help write my thoughts. The conclusion obtained is that animation is very much a good medium for conveying things like issues within our society because of its flexibility to be combined with other artistic media, thus helping the message that the author wanted to easily reach the audiences, and a good storytelling will made an impact to those who read/watch it even though they had finished the story till the end.